PENGARUH KEHANDALAN, ETOS KERJA DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAN PERIZINAN KABUPATEN POLEWALI MANDAR - Nawira, Andi (Indonesian Journal Of Economy Studies, 2022)
This study aims to test and prove empirically: (1) Is the reliability influence on employee satisfaction; (2) Is the work ethic influence on employee satisfaction; and (3) Is the discipline influence on employee satisfaction; Theoretically, this research is expected to enrich and complement the knowledge in the field of human resource management so as to be useful to academics and practitioners.The type of research is explanatory research, population and sample in the study were 57 employees. The samples using total sampling technique, were analyzed by linear regression analysis with software SPSS 23. The results showed that (1) Reliability positive and significant effect on employee satisfaction, employee reliability is needed in order to service to the public in this instance, an employee of a reliable working of course due to the high level of job satisfaction that you have on this intansi; (2) The work ethic positive and significant effect on job satisfaction of employees, each employee in the agency has a spirit called work ethic, this spirit which is then transformed into an attitude, for example discipline, high motivation, love of creating satisfaction with his job. Work ethic looks good employee job satisfaction reflect the high employee-owned; (3) Disciplinary positive and significant effect on employee satisfaction, employee job satisfaction owned can be seen from the level of employee discipline in everyday life, when employees arrive on time and to discipline employees it can be said to have a good job satisfaction. Vice versa, the discipline of an employee who does not reflect its lack of job satisfaction.